Pengaruh Konten Marketing dan Influencer terhadap Keputusan Pembelian Skincare Moell melalui Brand Image - Imron Parsaoran; Anggalia Wibasuri (Studi Ilmu Manajemen dan Organisasi, 2025)
Purpose: This study aims to analyze the influence of marketing content and influencers on the purchase decision of Moell baby skincare products, with brand image as a mediating variable. Methodology: This study uses a quantitative approach with a causal research design. The sampling technique uses purposive sampling with a sample of 100 people. Data were collected via a Google Form questionnaire and analyzed using smart-PLS. Result: Based on the results of the study, it can be concluded that marketing content has no effect on  the purchase decision of Moell's baby skincare products. Influencers have no influence on Moell's decision to purchase baby skincare products. Brand image affects  the purchase decision of Moell's baby skincare products. Conclusion: Brand image weakens the influence of marketing content on the purchase decision of Moell's baby skincare products and brand image can strengthen the influence of influencers on the purchase decision of Moell's baby skincare products. Limitations: This research also has limitations in the coverage of the area focused on the city of Bandar Lampung, so that future similar research can expand the scope of the research area to get better results. Contribution: marketing content and influencers because usually consumers increasingly believe that their skin condition or type is the same as the influencer so buying the recommended product and Moell skincare should always maintain the attractiveness of the influencer so that consumers always feel that the influencer who works with Moell skincare has an interesting and convincing speaking style.